2021
DOI: 10.1039/d1nj00602a
|View full text |Cite
|
Sign up to set email alerts
|

Improving the efficiency and stability of tin-based perovskite solar cells using anilinium hypophosphite additive

Abstract: Tin (Sn) is a potential replacement of lead in the organic-inorganic perovskite solar cells (PVSCs) technology due to the attractive optoelectronic properties of Sn-perovskites. However, the poor stability of Sn2+...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Adding reducing agents and antioxidants, such as hypophosphorous acid, , ascorbic acid (AA), formamidine sulfinic acid, etc., is an effective way to hinder the oxidation of Sn 2+ in the perovskite. We have found that the introduction of metallic Sn powders into Sn–Pb perovskite precursor ink suppresses the oxidation of Sn 2+ to Sn 4+ through a comproportionation reaction (Sn 4+ + Sn 0 → 2Sn 2+ ), resulting in improved performance and stability (Figure c) .…”
Section: Optimization Of Perovskite Absorbersmentioning
confidence: 99%
“…Adding reducing agents and antioxidants, such as hypophosphorous acid, , ascorbic acid (AA), formamidine sulfinic acid, etc., is an effective way to hinder the oxidation of Sn 2+ in the perovskite. We have found that the introduction of metallic Sn powders into Sn–Pb perovskite precursor ink suppresses the oxidation of Sn 2+ to Sn 4+ through a comproportionation reaction (Sn 4+ + Sn 0 → 2Sn 2+ ), resulting in improved performance and stability (Figure c) .…”
Section: Optimization Of Perovskite Absorbersmentioning
confidence: 99%
“…However, the poor stability of perovskite solar cells still limits their industrial application. [11][12][13][14] Besides the decomposition of the perovskite structure, the expensive organic hole transport materials (HTMs) also have unsatisfied long-term stability. Although many efforts have been focused on improving carrier mobility and reducing the cost of the materials, it is still significantly important to develop new HTMs to improve the stability of perovskite solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, defect free crystallization of Sn-based perovskite significantly impacts cell performance. Though several efforts have been made to tackle the aforementioned issues and prevent the occurrence of defects [18][19][20][21][22][23][24][25][26][27][28], there is still ample room for improvement as the maximum efficiency (13.24%) for SnX 3 -based perovskite solar cells (PSCs) [29] and stability reached at 3800 h [30] are still lower than its SQ limit.…”
Section: Introductionmentioning
confidence: 99%